THE ROLE OF GREEN TECHNOLOGIES AND SMART CITY PROJECTS (SYNERGY FOR A SUSTAINABLE FUTURE) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the context of growing global challenges related to climate change, urbanization and the need for sustainable development, green technologies and smart city projects play a decisive role in the transformation of modern societies. Their potential to reduce environmental footprints, optimize resources and improve quality of life makes them an integral part of strategies for a sustainable future. The study focuses on the interaction between green technologies and smart city projects. It aims to analyze the synergies between them, highlighting their potential and contribution to sustainable development. The following objectives have to be settled for reaching the above-mentioned goal: 1. to research the main characteristics and types of green technologies; 2. to analyze the principles and best practices of smart city projects; 3. to identify the opportunities for synergies between the two concepts in the context of sustainability; 4. to assess the environmental, economic and social benefits of the integration of these approaches; 5. to formulate recommendations for enterprises and the public sector on the implementation of green technologies in smart city systems. In the course of the study shall be justified the thesis that the integration of green technologies in smart city projects not only contributes to sustainable development, but also creates innovative platforms for effective natural resource management, pollution reduction and quality of life enhancement in urban areas. The methodology includes a comprehensive literature review, structured interview, needs analysis, gap analysis and SWOT analysis. The expected results are: clarification of the relationship between green technologies and smart city projects; assessment of successful examples of synergies between these approaches; formulation of recommendations for business and public sector to support their implementation; identification of the main challenges and barriers related to the integration of the researched innovations.